Improvement of the General Resilience of Social–Ecological Systems on an Urban Scale Through the Strategic Location of Urban Community Gardens - Dovile Kukukaite; Miguel Ángel Bartorila; Claudia Gutiérrez-Antonio (Urban Science)
Urban community gardens are spaces where human well-being is improved by generating ecosystem services locally, and the interactions between humans and the environment increase the resilience of social–ecological systems. Their advantages locally have already been demonstrated. Yet, their effects on larger scales are not clear. According to the panarchy principle, a resilient subsystem may improve the resilience of a whole system. The complex interactions between different scales are one of the challenges in the search for resilience in urban systems. With this research, we provide conceptual interscalar leverage points in urban planning to foster resilience. We postulate that strategically located urban community gardens enhance the general resilience of social–ecological systems on an urban scale by applying a qualitative method to approach the general resilience of a place and the cartography of general urban-landscape resilience. We applied these methods in five urban segments of Queretaro, Mexico. The case study of the Mu’ta urban community garden helps us demonstrate the changes in its general resilience with the emergence of a garden. The results confirmed the resilience influences between the scales of locality, neighborhood, and city through the social–ecological overlap, spatial continuity, and heterogeneity in the density of landscape openness to engage socially and ecologically.